2004
DOI: 10.1071/ap04054
|View full text |Cite
|
Sign up to set email alerts
|

Host range, symptom expression and RNA 3 sequence analyses of six Australian strains ofCucumber mosaic virus

Abstract: G The first two authors contributed equally to this work.Abstract. We have characterised six Australian Cucumber mosaic virus (CMV) strains belonging to different subgroups, determined by the sequence of their complete RNA 3 and by their host range and the symptoms they cause on species in the Solanaceae, Cucurbitaceae and on sweet corn. These data allowed classification of strains into the known three CMV subgroups and identification of plant species able to differentiate the Australian strains by symptoms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…In newly developing tomato leaves, viral isolate induced symptoms ranging from severe chlorotic patches, downward curling and reduced leaf lamina to mild filiformism. Previously, shoestring like leaves symptoms were reported only with some subgroup I strains [2,20,32,46,48]. From India also there was report of mosaic symptoms on tomato by subgroup II strain [47] and now in a recent observation it was found that shoestring symptoms were not restricted to subgroup I.…”
Section: Discussionmentioning
confidence: 90%
“…In newly developing tomato leaves, viral isolate induced symptoms ranging from severe chlorotic patches, downward curling and reduced leaf lamina to mild filiformism. Previously, shoestring like leaves symptoms were reported only with some subgroup I strains [2,20,32,46,48]. From India also there was report of mosaic symptoms on tomato by subgroup II strain [47] and now in a recent observation it was found that shoestring symptoms were not restricted to subgroup I.…”
Section: Discussionmentioning
confidence: 90%
“…Shoe-string symptoms caused by CMV has been reported from India, which was grouped under subgroup-IB [14], whereas CMV isolated from tomato showing shoe-string in Pakistan [2] and Australia [30] were grouped under subgroup-IA and -IB, respectively. In the present study, CMV isolate showing shoe-string in tomato (Tss-In) is grouped under subgroup-II.…”
Section: Discussionmentioning
confidence: 97%
“…Proteins 1a, 2a and 3a are expressed from genomic RNAs 1, 2 and 3 respectively, whereas the coat protein (CP) and 2b proteins are expressed from subgenomic RNA4 and RNA 4A, respectively (Palukaitis et al 1992;Ding et al 1994;Sulistyowati et al 2004). The 1a and 2a proteins are apart of viral replicase complex (Hayes and Buck 1990), while cell to cell movement through the plant requires the 3a movement protein (MP) and coat protein (CP) (Suzuki et al 1991;Taliansky and Garcia-Arenal 1995;Kaplan et al 1995;Gal-On et al 1998).…”
Section: Introductionmentioning
confidence: 97%
“…Tomato is found to be infected with all three subgroups of CMV (Sudhakar et al 2006;Akhtar et al 2008;Pratap et al 2008). CMV infected plants show a broad spectrum of symptoms from mild to severe mosaic, stunting, filiformity, chlorosis and necrosis depending on viral strain and host (Carrere et al 1999;Sulistyowati et al 2004;García-Arenal and Palukaitis 2008). In tomato, some subgroup I strains can cause fern-shaped filiform leaves and stunting (Hellwald et al 2000;Stamova and Chetelat 2000;Akhtar et al 2008;Pratap et al 2008) whereas subgroup II strains lead to severe mosaic, leaf puckering and stunting (Sudhakar et al 2006).…”
Section: Introductionmentioning
confidence: 97%